Vascular ring anomalies in cats: 20 cases (2000‐2018). Issue 2 (9th October 2019) - Bascuñán, Ana; Regier, Penny J.; Case, J. Brad; Singh, Ameet; Balsa, Ingrid; Flanders, James; Thieman‐Mankin, Kelley; Ham, Kathleen M.
Abstract: Objective: To report the clinical characteristics, types of vascular ring anomalies (VRA), operative findings, complications, and survival after surgical treatment of cats with VRA. Study design: Retrospective, multi‐institutional case series. Animals: Client‐ or shelter‐owned cats presenting to academic, referral veterinary institutions. Methods: Medical records of cats with VRA that underwent surgical treatment were reviewed. Signalment, relevant medical history, clinical signs, diagnostic imaging, surgical findings, complications, and survival were recorded. Results: Twenty cats with VRA were included. Vascular ring anomalies were most commonly (75% [15/20]) diagnosed in cats less than 1 year old, with no breed or sex predilection. Regurgitation was the most common clinical sign, present in 18 of 20 (90%) cats. A persistent right aortic arch was diagnosed in 17 of 20 (85%) cats, with concurrent aberrant left subclavian artery in four of the cats. Surgical treatment was associated with survival to discharge in 18 of 20 (90%) cats. Persistent clinical signs were reported in nine of 13 (69%) cats, and radiographic evidence of megaesophagus persisted in four of 13 (31%) cats, with a median follow‐up of 275 days after discharge. Conclusion: Persistent right aortic arch was the most commonly diagnosed VRA in cats in this series, although multiple anomalies were observed. Surgical treatment of VRA in cats was associated with a high survival to discharge, although persistence of clinical signs and megaesophagus was noted in 69% and 31% of the cats, respectively. Clinical significance: Surgical treatment of VRA in cats is associated with a high survival rate; however, persistence of clinical signs is an expected outcome.